Effects of Irradiation by UV- Acceleration on Mechanical Properties of Polymer Blends (Polyester: Starch) - Salih, Sihama I.; Hamad, Qahtan A.; Jabbar, Safaa N. Abdul; Sabit, Najat H. (Al-Nahrain Journal for Engineering Sciences, 2018)
This work covers mixing of unsaturated polyester (un- polyester) with starch powders as polymer blends and study the effects of irradiation by UV-acceleration on mechanical properties of its. The unsaturated polyester was mixing by starch powders at particle size less than (45 µm) at selected weight fraction of (0, 0.5, 1, 1.5, 2, 2.5 and 3%). These properties involve ultimate tensile strength, modulus of elasticity, elongation percentage, flexural modulus, flexural strength, fracture toughness, impact strength and hardness. The results illustrate decrease in the ultimate tensile strength at and elongation percentage, while increasing modulus of elasticity, with increasing the weight ratio of starch powder to 3 % weight fraction, whereas the maximum value of hardness and flexural, impact properties happened at 1 % weight fraction for types of polymer blends.